Strategi Pengembangan Kawasan timur Indonesia: Isu Pokok, Kebijaksanaan dan Program Pembangunan - Bambang Bintoro Soedjito (The Institute for Research and Community Services, Institut Teknologi Bandung, 1995)
The strategy of Eastern Indonesia's development is based on the abundant of natural resources ¡n some provinces, small number of population with unequal distribution, and government commitment in development equity. The strategy of Eastern Indonesia's development is a hierarchical policy from micro level, meso level to macro level. Micro strategy is intended to recognize and fulfill the basic needs, help the economic of the region to be self-sufficient and enhance local export. Meso strategy is intended to recognize the physical and economic correlation among the provinces to create interregional development centers in the related area. Meanwhile the macro strategy is focused more on the development of transportation infrastructure, natural resources utilization and environmental preservation, increase private participation, strengthening government and public agencies including the involvement of universities in order to increase the quality of human resources in Eastern Indonesia